Studying the History of Social Science Data Archives as Knowledge Infrastructure - Downey, Greg; Eschenfelder, Kristin R.; Shankar, Kalpana (My University, 2016)
We map out a new arena of analysis for knowledge and cyberinfrastructure scholars: Social Science Data Archives (SSDA). SSDA have influenced the international development of the social sciences, research methods, and data standards in the latter half of the twentieth century. They provide entry points to understand how fields organise themselves to be ?data intensive?. Longitudinal studies of SSDA can increase our understanding of the sustainability of knowledge infrastructure more generally. We argue for special attention to the following themes: the co-shaping of data use and users, the materiality of shifting revenue sources, field level relationships as an important component of infrastructure, and the implications of centralisation and federation of institutions and resources. We briefly describe our ongoing study of primarily quantitative social science data archives. We conclude by discussing how cross-institutional and longitudinal analyses can contribute to the scholarship of knowledge infrastructure.
Keywords: social science data; knowledge infrastructure; data sharing; data archive